Institutional Dynamics and Employee Engagement: A Multi-Site Phenomenological Investigation of Administrative Staff Experiences within Public Higher Education Institutions in Ghana - Abilla-Buame, Juliana (Advances in Social Sciences Research Journal, 2025)
This study explores the lived experiences of administrative staff regarding workplace engagement within Ghanaian public universities, addressing a significant gap in understanding how institutional dynamics influence engagement levels in resource-constrained higher education settings. Through a phenomenological lens, the research examines how organizational structures, culture, and motivational factors shape administrative staff engagement. The study employed a qualitative research design, utilizing semi-structured interviews with 45 administrative staff across multiple public universities in Ghana. Data collection involved in-depth interviews, focus group discussions, and document analysis, with data analyzed using Interpretative Phenomenological Analysis (IPA). Key findings reveal that institutional structures significantly influence engagement levels, with organizational communication patterns and decision-making processes emerging as critical factors. The study identified four primary themes: institutional structures (45 mentions), motivational factors (30 mentions), engagement initiatives (25 mentions), and barriers to engagement (20 mentions). Resource constraints and cultural factors were found to significantly impact engagement levels and implementation of engagement initiatives. The research contributes to both theoretical understanding and practical application of employee engagement in public higher education institutions. Findings suggest the need for contextualized engagement strategies that consider resource constraints and cultural dimensions. Future research should explore the impact of technological integration on administrative staff engagement and examine the relationship between engagement levels and institutional performance metrics in resource-constrained environments.